Suicide in the Early Stage of Schizophrenia - Ventriglio, Antonio; Gentile, Alessandro; Bonfitto, Iris; Stella, Eleonora; Mari, Massimo; Steardo, Luca; Bellomo, Antonello (Frontiers in Psychiatry, 2016)
Suicide is a relevant leading cause of death among patients affected by schizophrenia. Even if suicidal ideation may be present in different stages of disease, some differences have been described between the risk of suicide in patients experiencing first-episode of psychosis and those with long-term schizophrenia. It is particularly higher during the first year of illness and reaches a steady decline over the following years. Suicidal ideation and attempts may also be common among subjects with subthreshold psychotic experiences. Factors associated with the risk of suicide in the early phase of schizophrenia are previous suicidal attempts and social aspects: the lack of social support and stable relationships, social drift after the first- episode, social impairment. Also, several psychotic symptoms (suspiciousness, paranoid delusions, mental disintegration and agitation, negative symptoms, depression and hopelessness, command hallucinations) and substance abuse are associated to higher risk of suicide. It has been described that perfectionism and good levels of insight among individuals who have recently developed psychotic symptoms are significantly associated to higher numbers of suicidal attempts. Moreover, recent evidences show that prefrontal- cortex- based circuit dysfunction may be related to suicide in the early stage of schizophrenia. This narrative review summarizes available evidences on suicide in the early stage of schizophrenia and deals with issues to be further studied and discussed.